Primary adrenal insufficiency due to hereditary apolipoprotein AI amyloidosis: endocrine involvement beyond hypogonadism. (3rd April 2018) - Pané, Adriana; Ruiz, Sabina; Orois, Aida; Martínez, Daniel; Squarcia, Mattia; Sastre, Lydia; Ruiz, Pablo; Caballería, Joan; Mora, Mireia; Hanzu, Felicia A.; Halperin, Irene
Abstract: Several mutations in the gene encoding apolipoprotein AI (apoAI) have been described as a cause of familial amyloidosis. Individuals with apoAI-derived (AApoAI) amyloidosis frequently manifest with liver, kidney, laryngeal, skin and myocardial involvement. Although primary hypogonadism (PH) is considered almost pathognomonic of this disease, until now, primary adrenal insufficiency (PAI) has not been described as a common clinical feature. Here, we report the first kindred with AApoAI amyloidosis in which PAI is well-documented. All family members with the Leu60_Phe71delins60Val_61Thr heterozygous mutation who were regularly followed-up at our centre were considered. Nineteen individuals had the confirmed APOA1 deletion/insertion mutation, with detailed medical records available in 11 cases. Of these, 6 had PAI and 3 (all males) had PH. Among them, one 47-year-old man, not previously diagnosed with PAI, developed adrenal crisis after liver transplantation, precipitated by an opportunistic infection. Transplantation due to organ failure, which necessitates use of immunosuppressive medication such as corticosteroids, is frequently required during the course of hereditary amyloidosis. Consequently, PAI can remain masked, being discovered only when an adrenal crisis develops. Therefore, according to the present evidence, patients with AApoAI amyloidosis should be submitted to regular testing of corticotrophin and cortisol levels in order to avoid delaying corticosteroid replacement.